Role Play-Based Learning of Religious Education for Students'empathy on Peace & Harmony - Musnandar, Aries; Aziz, Sumarno (Proceedings of Annual Conference for Muslim Scholars, 2022)
Role Play-Based Learning of Religious Education for Students'empathy on Peace & Harmony